Legal Analysis of the Principle of Legal Certainty in Tax Collection and Settlement in Indonesia - Hendy; I Made Kanthika; Horadin Saragih; Malemna Sura Anabertha Sembiring (GoAcademica Research & Publishing, 2026)
Taxation is a fundamental source of state revenue and plays a crucial role in supporting national development. Consequently, tax collection must be based on legal principles that ensure justice, efficiency, and legal certainty. In practice, tax disputes frequently arise due to differences in the interpretation and application of tax regulations, as well as issues related to dispute resolution mechanisms. This study examines the implementation of the principle of legal certainty within Indonesia’s tax collection system and tax dispute resolution framework, and evaluates the extent to which tax legislation provides legal protection for both taxpayers and tax authorities. The research focuses on a tax dispute between PT MSJ (Mitra Sinar Sejahtera) and the Directorate General of Taxes concerning the issuance of a Tax Collection Letter. Using a normative juridical research method, this study analyzes relevant tax laws and regulations, legal doctrines, and court decisions. The findings indicate that Indonesia’s tax collection and dispute resolution systems are formally grounded in the principle of legal certainty. Practical challenges persist, particularly inconsistencies in legal interpretation and discrepancies between statutory provisions and administrative practices, which may lead to tax disputes and weaken taxpayer confidence in the national tax system. Strengthening legal certainty in taxation requires regulatory harmonization, improved transparency in tax governance, and consistent law enforcement to ensure a fair and predictable tax system.